Lifestyle patterns of students entering the University of Huanuco - Ruiz-Aquino, Mely (2019)
Objective. to determine the lifestyle patterns of students entering the university of huánuco. Methods. the study was quantitative, observational and transversal, with a descriptive-comparative design. the population consisted of 1752 university students entering the university in 2019; from which a sample of 315 subjects was extracted, probably selected by strata. a survey guide of general characteristics and a scale of lifestyle patterns, previously validated, were applied. a descriptive and inferential analysis was performed using the chi-square test. Results. 67.6 % (213) had healthylifestyle patterns. when analyzing the patterns of lifestyles, according to dimensions, it was evidenced that 56.8 % (179) of the students, had unhealthy eating habits, and 53.7 % (169) of the sample evidenced sedentarism. there were healthy life patterns in the mental health dimensions [95.9 % (302)]. and recreation [80.3 % (253)]. when contrasting the hypotheses of the study, statistical significance was found [x2 = 5.250; p = 0.015] between healthy lifestyle and the practice of some sport. no significance was found between lifestyle and adolescent group membership (x2 = 1.121; p =  0.186), marital status [x2 = 0.003; p = 0.632] and sample gender [x2 = 0.872; p = 0.209]. Conclusions. healthy lifestyle patterns are conditioned by the practice of sport.